2017
DOI: 10.1016/j.nucengdes.2017.04.037
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty analysis of PKL SBLOCA G7.1 test simulation using TRACE with Wilks and GAM surrogate methods

Abstract: The Nuclear Energy Agency auspices simulation of experiments in different facilities under several programs. One on them consisted of performing a counterpart test between ROSA/LSTF and PKL facilities, with the main objective of determining the effectiveness of late accident management actions in a small break loss of coolant accident. The results obtained by TRACE code for PKL experiment SBLOCA G7.1 (a scaled model of Konvoi reactor) were in good agreement with the experiments. However, in the simulation proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…The pioneering BEPU methodology was code scaling, applicability, and uncertainty (CSAU) [8], sponsored by the USNRC, where the propagation of uncertainty to the results was performed using a surrogate model of the thermo-hydraulic code, namely a polynomial response surface. Around the turn of the century, a new type of propagation procedure gained acceptance, based on the original code and on the calculation of tolerance limits using nonparametric Wilks' method [9,10]. A method called advanced statistical treatment of uncertainty method (ASTRUM) is one of the typical methodologies based on Wilks' theory.…”
Section: Bepu Methodsmentioning
confidence: 99%
“…The pioneering BEPU methodology was code scaling, applicability, and uncertainty (CSAU) [8], sponsored by the USNRC, where the propagation of uncertainty to the results was performed using a surrogate model of the thermo-hydraulic code, namely a polynomial response surface. Around the turn of the century, a new type of propagation procedure gained acceptance, based on the original code and on the calculation of tolerance limits using nonparametric Wilks' method [9,10]. A method called advanced statistical treatment of uncertainty method (ASTRUM) is one of the typical methodologies based on Wilks' theory.…”
Section: Bepu Methodsmentioning
confidence: 99%
“…This work mainly researches the uncertainty of input parameters, and their distributions are determined through PIRT and related literature research (Zhujian and Shoulv, 1992;Gupta et al, 2013;Sanchez-Saez et al, 2017). 9.…”
Section: Reference the Phenomena Identification And Rankingmentioning
confidence: 99%
“…Many researchers used the BEPU method to analyze SBLOCA. Sanchez-Saez et al (2017) presented a methodology and the application to G7.1 experiment. They performed uncertainty analysis of PKL SBLOCA G7.1 test simulation using TRACE with Wilks' and GAM surrogate methods and found that for larger sample sizes, GAMPE and Wilks' results present similar performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, uncertainty analysis was performed to find the key parameters affecting the system performance, research the uncertainty propagation rules, and evaluate the precision of codes. Uncertainty analysis has been widely used in the field of nuclear engineerings, such as system simulation, 23‐25 multidimensional CFD, 21,26‐29 and reactor physics calculation 30,31 …”
Section: Introductionmentioning
confidence: 99%